Intrinsic and instrumental perspectives to sanitation. (August 2018) - Jain, Anoop; Subramanian, S.V.
Abstract: Public health interventions are often implemented because they are a means to an end. For example, improving population-level health outcomes is a key step towards improving social and economic outcomes, too. But what is often overlooked is the fact that a given public health intervention might be the end in itself. In other words, a given intervention might be worth investing in even if there are zero returns from investing in it. This intrinsic value, however, is often overlooked. In this commentary, we look specifically at sanitation, and why the development community should motivate sanitation interventions using an intrinsic value perspective. We also extend the conversation to why there needs to be a fundamental shift away from demand-side interventions to supply-side interventions. In doing so, we hope to offer a more equitable perspective to health and development.